Una introducción al pensamiento de Anthony Giddens - Andrade Carreño, Alfredo; Farfán Hernández, Rafael; Girola Molina, Lidia, coordinadora; Girola Molina, Lidia; Kozlarek, Oliver; Murguía Lores, Adriana; García Andrade, Adriana (Universidad Autónoma Metropolitana, Unidad Azcapotzalco, División de Ciencias Sociales y Humanidades, Departamento de Sociología, 2015)
1 archivo PDF (135 páginas)